2018
DOI: 10.1002/hep.30050
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Peginterferon Alfa‐2a (40KD) in Children With Chronic Hepatitis B: The PEG‐B‐ACTIVE Study

Abstract: Children with chronic hepatitis B (CHB) represent an area of unmet medical need, attributed to increased lifetime risk of CHB sequelae and limited therapeutic options compared with adult CHB patients. The PEG-B-ACTIVE (NCT01519960) phase III study evaluated peginterferon (PegIFN) alfa-2a treatment in children aged 3 to <18 years with CHB. A total of 161 hepatitis B e antigen (HBeAg)-positive immune-active patients without advanced fibrosis (AF)/cirrhosis were randomized (2:1) to PegIFN alfa-2a (Group A, n = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 37 publications
(81 reference statements)
3
35
0
2
Order By: Relevance
“…The phase III of the clinical study on PegIFNα‐2a for antiviral treatment in children with CHB showed that children had higher HBsAg clearance rate after drug discontinuation than did adults (8.9% vs 3%) when treated with PegIFNα‐2a. Zhu et al reported the efficacy of PegIFNα‐2a in the treatment of 45 cases of Chinese children with HBeAg‐positive CHB (96 weeks), and the 96‐week HBeAg and HBsAg seroconversion rates were 91.9% and 18.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phase III of the clinical study on PegIFNα‐2a for antiviral treatment in children with CHB showed that children had higher HBsAg clearance rate after drug discontinuation than did adults (8.9% vs 3%) when treated with PegIFNα‐2a. Zhu et al reported the efficacy of PegIFNα‐2a in the treatment of 45 cases of Chinese children with HBeAg‐positive CHB (96 weeks), and the 96‐week HBeAg and HBsAg seroconversion rates were 91.9% and 18.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are relatively fewer reports on predictors for efficacy in children. Phase III clinical trials on children treated with PegIFNα‐2a found that the efficacy was better among patients with baseline ALT of 2‐5 ULN than among those with baseline ALT of 5‐10 ULN. Multivariate regression analysis for the present study showed that genotype B ( P = 0.0135), body weight < 25 kg ( P = 0.0369) or between 25 kg and 45 kg ( P = 0.0260) and decrease in HBsAg level by >1 log ( P < 0.0001) after 24 weeks of treatment were independent predictors for HBsAg clearance at the end of the follow‐up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, IFNa can achieve a functional cure in adults without generating any drug resistance, although the efficacy is low at below 5% . However, the efficacy of IFNa treatment has only been tested in children with CHB recently …”
Section: Introductionmentioning
confidence: 99%
“…Complicating this issue is that paediatric patients usually show normal ALT levels even when in the active immune stage as defined by liver biopsies . In a recent study evaluating the efficacy and safety of PEG‐IFNa in children with CHB, young patients with ALT levels <2‐fold the ULN also achieved hepatitis B e antigen (HBeAg) seroconversion after IFNa treatment . This further suggested that the current guideline for IFNa treatment, which is mainly based on observations from adult CHB patients, needs to be reexamined.…”
Section: Introductionmentioning
confidence: 99%